AB0625 Autoantibody profile in patients diagnosed with idiopathic inflammatory myopathy: multicenter registry on inflammatory myositis from the rheumatology society in madrid, spain. (15th June 2017) - Hernández Flόrez, DC; Valor, L; Martinez, J; Joven, B; Nuno, L; Larena, C; Llorente, I; Barbadillo, C; Pena, P Garcia de la; Ruiz, L; Moruno, H; Cobo, T; et al.
Abstract : Background: Inflammatory myopathies (IIM) are a heterogeneous group of autoimmune rheumatic diseases characterized by muscle inflammation and progressive weakness. They include any kind of primary inflammatory muscle disease that is not otherwise better explained by metabolic, toxic, infectious, neurologic or inherited causes. The presence of autoantibodies (AA) in IIM is variable and they can recognize nuclear and cytoplasmic cellular components. Objectives: To evaluate the AA profile in patients diagnosed with IIM. Methods: We evaluated 479 patients that included 12 hospitals belonging to the IIM registry of the Rheumatology Society in Madrid (SORCOM-REMICAM) with diagnosis from January 1980 to December 2014. All patients were diagnosed of IIM according to Bohan and Peter criteria. The AAs evaluated were ANA (n=476), anti-Jo1 (n=457), anti-RNP (n=427), anti-MI2 (n=159) and ACA (n=293), according to the standard techniques in the respective laboratories. The presence of ANA was considered valid with at least two positive determinations. The AAs were compared according to the classification I) as dermatomyositis (primary and secondary dermatomiositis) (DM) and polymyositis (PM) including the rest of the patients. Also, IIM were classified (II) as primary polimiositis (PPM), primary dermatomyositis (PDM), overlap syndrome (OSd), juvenile myopathies (JM), cancer-associated myopathies (CAM), autoimmune necrotizing myopathy and inclusion body myositis (these were grouped as other myositis; OM). Results: In the PM and DM groups 250 and 229 (52.2% and 47.8%) patients were included respectively. Positive ANA, anti-Jo1 and anti-RNP were higher in the PM than in the DM group (67, 22 and 19% vs. 56, 11 and 6%) (p=0.21, p=0.002, p=0.0001, respectively). The presence of anti-MI2 was higher in the DM group (p=0.024), according to the classification II, we found statistically significant differences in ANA, anti-Jo1, anti-RNP and anti-ACA. The OSd group had the highest proportion of ANA, anti-RNP and ACA positive AA and the JM group had the lowest frequency of Anti-Jo1 (see Table 1 ). Conclusions: The AA associated with the IIM subtypes is consistent with published scientific evidence on other cohorts for ANA, anti-Jo1, anti-RNP and anti-MI2, in spite of the small sample size. The OSd group showed higher ANA and anti-RNP frequencies which might be explained by the coexistence of SLE and MCTD patients. It could be interesting to follow up those PPM patients with positive AA because they could be in the future diagnosed with a connective tissue disease. Carrying out longitudinal studies that include a greater proportion of patients may help to evaluate and predict the clinical course of IIM. References: Bohan A, Peter JB. N Engl J Med 1975 Feb 13;292(7):344–7. Acknowledgements: . Disclosure of Interest: None declared